Multilingual Families in a Digital Age Mediational Repertoires and Transnational Practices - Lexander, Kristin Vold (Routledge Critical Studies in Multilingualism, 2023)
language and identity; language and communication; digital interaction; digital language practices; semiotic resources; sociolinguistics